In Situ X-Ray Study During Thermal Cycle Treatment Combined with Complementary Ex Situ Investigation of InGaN Quantum Wells - Ewa Grzanka; Sondes Bauer; Artur Lachowski; Szymon Grzanka; Robert Czernecki; Byeongchan So; Tilo Baumbach; Mike Leszczyński (Nanomaterials)
In situ X-ray reciprocal space mapping was performed during the interval heating and cooling of InGaN/GaN quantum wells (QWs) grown via metal–organic vapor phase epitaxy (MOVPE). Our detailed in situ X-ray analysis enabled us to track changes in the peak intensities and radial and angular broadenings of the reflection. By simulating the radial diffraction profiles recorded during the thermal cycle treatment, we demonstrate the presence of indium concentration distributions (ICDs) in the different QWs of the heterostructure (1. QW, bottom, 2. QW, middle, and 3. QW, upper). During the heating process, we found that the homogenization of the QWs occurred in the temperature range of 850 °C to 920 °C, manifesting in a reduction in ICDs in the QWs. Furthermore, there is a critical temperature (T = 940 °C) at which the mean value of the indium concentration starts to decrease below 15% in 1. QW, indicating the initiation of decomposition in 1. QW. Moreover, further heating up to 1000 °C results in extended diffuse scattering along the angular direction of the diffraction spot, confirming the propagation of the decomposition and the formation of trapezoidal objects, which contain voids and amorphous materials (In-Ga). Heating InGaN QWs up to T = 1000 °C led to a simultaneous decrease in the indium content and ICDs. During the cooling phase, there was no significant variation in the indium concentrations in the different QWs but rather an increase in the defect area, which contributes to the amplification of diffuse scattering. A comparison of ex situ complementary high-resolution transmission microscopy (Ex-HRTEM) measurements performed at room temperature before and after the thermal cycle treatment provides proof of the formation of four different types of defects in the QWs, which result from the decomposition of 1. QW during the heating phase. This, in turn, has strongly influenced the intensity of the photoluminescence emission spectra without any detectable shift in the emission wavelength λMQWs.